Table of Content - - (Journal of medical and pharmaceutical sciences, 2024)
Table of Content: 1. Innovations and Challenges in Modern Ambulance Services Mr. Alhassan Hamad Almass, Mr. Mana Mohammed Yaseen, Mr. Hussein Salem Al Mansour, Mr. Ali Salem Al Shaiban, Mr. Salaiman Turki Al Saab, Mr. Ali Moeed Almansour, Mr. Fahad Mohammad Zbid, Mr. Nawaf Mana Al Dwis 2. Studying the Knowledge, Attitude, and Practice of HealthCare Workers Towards Hepatitis B Virus Prevention in Hospitals, Hodeidah City, Yemen, 2024 Dr. Mogeeb Saeed Taha, Dr. Sadeq Abdo Mohammed Al-Wesabi, Dr. Khaled Al-Selwi, Dr. Mohammed Ahmed Suhail, Dr. Radman Ahmed Al-Nahary, Dr. Abdulaziz Ahmed Baalwi, Dr. Nabil Ahmed Saif Ghanim 3. First aid education in schools Mr. Hashil Hassan Al Hashil, Mr. Hassan Salem Al Hashil, Mr. Musalli Naji Al Alhareth , Mr. Hussein Yahya Al Mansour , Mr. Yaseen Mesfer Al Hutayla